Classroom management practices of teachers in Laperian Elementary School: Basis for an enhanced intervention program - Jackie Lyn T. Tutor; Nimfa G. Siaton; Rhean Dee C. Ecoy; Shemma Mae A. Marianito; Ma. Jenesa D. Ano-os (Eureka: Journal of Educational Research, 2026)
In elementary education, creating classroom management is essential because it helps young learners to have the structure, guidance, and engagement that they need in order to learn. This study focused on classroom management practices of all 30 elementary teachers at Laperian Elementary School in Tukuran, Zamboanga del Sur for School Year 2024-2025. This newly conducted study used a descriptive-correlational research design with the total population sample technique, and the 40 item validated structured questionnaire covers four domains: classroom organization, behavior management, instructional management and teacher-student relationships. Data were collected by means of paper-based questionnaires and analyzed by descriptive statistics (mean & standard deviation) and Pearson Product-Moment Correlation. Qualitative data was coded using thematic analysis, for open-ended responses. Findings indicated an overall high level of classroom management practice (M=4.30, SD=0.43). Teachers rated teacher-student relationships the highest (M=4.45, Very High) and instructional management the lowest (M=4.15, High) among the four domains. Classroom management practices were positively and significantly correlated with number of years of teaching experience (r=0.52, p=0.003) and attended trainings respectively (r=0.61, p=0.001). Qualitative results underscored the value of building rapport, difficulties in differentiating for diverse learners within multigrade classes, and significant demand for ongoing professional development. From these findings, an improved intervention program is recommended, promoting instruction management by differentiated and adaptable teaching methods as well continuing of contextualized on professional development interventions for the rural elementary teachers.